Estudio del balance hídrico en la subcuenca del río Chambo usando el modelo SWAT - Gunsha Chicaiza, Jhoselyn Valeria (2026)
This research analyzes the hydrological behavior and adaptive capacity of the Chambo River sub-basin from 1980 to 2021. It considers evidence of climate change and human activities, such as changes in vegetation cover resulting from agriculture and urban growth. These factors affect both soil and water. The main objective is to characterize climatic and hydrological trends and quantify the overall water balance. The SWAT (Soil and Water Assessment Tool) hydrological model was used. Daily data on precipitation, temperature, relative humidity, wind speed, and solar radiation from local stations served as input. This data was used to calibrate the model and simulate climate, soil, and land cover conditions in the Chambo River sub-basin. The model produced the flow rate at the outlet of the study area. The research addresses the lack of water resources information in Chimborazo province. Water is essential for daily life in this and other locations. Therefore, it must be quantified and analyzed to determine whether the amount entering and leaving the system is balanced